2012
DOI: 10.1590/s0103-51502012000200008
|View full text |Cite
|
Sign up to set email alerts
|

Análise do equilíbrio estático em crianças com paralisia cerebral do tipo diparesia espástica com e sem o uso de órteses

Abstract: INTRODUÇÃO: Crianças com paralisia cerebral (PC) do tipo diparesia espástica são frequentes usuárias de órteses para membros inferiores, com a finalidade de proporcionar melhora funcional da postura ortostática e durante a marcha. OBJETIVO: Analisar o equilíbrio estático de crianças diparéticas espasticas com PC, com e sem uso de órteses, por meio de parâmetros estabilométricos. MATERIAIS E MÉTODOS: A amostra foi composta por 15 indivíduos com idades entre 4 e 14 anos (médias de 8,33 ± 2,74), sete do s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
6

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 27 publications
0
5
0
6
Order By: Relevance
“…However, for children with paresis CP, although they have motor impairment in the upper limbs, the impairment predominance is in the lower limbs, which justifies the most common indication orthosis for LL. According to Roque et al (2012), orthoses for LL are frequently used by children with spastic CP paresis to provide functional improvement of orthostatic posture and gait.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, for children with paresis CP, although they have motor impairment in the upper limbs, the impairment predominance is in the lower limbs, which justifies the most common indication orthosis for LL. According to Roque et al (2012), orthoses for LL are frequently used by children with spastic CP paresis to provide functional improvement of orthostatic posture and gait.…”
Section: Discussionmentioning
confidence: 99%
“…For 83.3% of caregivers, the child felt safe with the orthosis, especially in the lower limbs. Studies performed with children with CP using orthoses showed that these children had better performance in the qualitative aspects of gait when with orthoses than without orthoses, considering that the orthosis guarantees greater stability and safety in the support phase (ROQUE et al, 2012;CURY et al, 2006;SCHWARTZMAN, 2004).…”
Section: According Tomentioning
confidence: 99%
“…A principal alteração apresentada por crianças com PC é o comprometimento motor, com consequentes alterações na biomecânica corporal, e um importante meio de auxílio para correção dessas alterações são as órteses 9 . O suporte mecânico oferecido pela órtese suropodálica, por exemplo, visa minimizar ou corrigir o padrão equino, proporcionando melhora no padrão de marcha, com menor gasto energético e melhor qualidade de vida; essa órtese é indicada para a sustentação de um segmento do corpo ou para a inibição de movimentos involuntários, tendo como objetivos aumentar a função, prevenir deformidades e contraturas, manter as extremidades em posição funcional, auxiliar a função da musculatura fraca e facilitar o controle motor seletivo 10 .…”
Section: Discussionunclassified
“…Abnormalities in muscle tone and, consequently, in posture, are common in children with CP, spasticity being the most 2 predominant. For this reason, the primary change on CP is the motor impairment, which leads to postural adjustments, with alterations on body biomechanics and possible bone deformities 3 . The constant action of distinct forces on the plantar surface may compromise foot functionality, leading to changes in load distribution.…”
Section: Introductionmentioning
confidence: 99%
“…The constant action of distinct forces on the plantar surface may compromise foot functionality, leading to changes in load distribution. These changes interfere with the alignment of ankle and foot and can lead to the emergence of plantar diseases and deformities 3,4 . This distribution analysis is relevant to the prevention of postural disorders 5,6 and can be performed with electronic baropodometry 7 , which gives an indication of foot function and helps the investigation of abnormal patterns in static position and gait, thus contributing to the disorders' understanding 4 .…”
Section: Introductionmentioning
confidence: 99%